2017
DOI: 10.1515/ijame-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady MHD Mixed Convection Flow of a Micropolar Fluid Over a Vertical Wedge

Abstract: An analysis is presented to investigate the unsteady magnetohydrodynamic (MHD) mixed convection boundary-layer flow of a micropolar fluid over a vertical wedge in the presence of thermal radiation and heat generation or absorption. The free-stream velocity and surface temperature are assumed to be oscillating in magnitude but not in the direction of the oncoming flow velocity. The governing equations have been solved by two distinct methods, namely, the finite difference method for the entire frequency range, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Based on the above assumptions, the governing equations of the current modeled problem are as follows [4,16,17]:…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above assumptions, the governing equations of the current modeled problem are as follows [4,16,17]:…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…MHD mixed convection micropolar uid ow through a rectangular duct was studied by Ayano et al [15], and they observed that the ow reversal increased and velocity decreased as the magnetic eld was intensi ed. Roy and Gorla [16] analyzed the time-dependent MHD micropolar uid past a wedge, and explored that the magnetic eld parameter considerably a ected the amplitude of the drag coe cient. Hsiao [17] analyzed the MHD micropolar nano uid with viscous e ects.…”
Section: Introductionmentioning
confidence: 99%
“…El-Aziz [12] analyzed the unstable combined convective of a micropolar fluid neighboring the hot orthogonal surface since the viscid dispersion exists. Roy and Gorla [13] studied the magnetohydrodynamicmixed convectionflow of a micropolar fluid along with an orthogonal wedge. Adnan [14] explained the combined convection past a level plate for a micropolar fluid in a boundary-layer flowing situation.…”
Section: Introductionmentioning
confidence: 99%
“…Zeeshan and Majeed (2016a, 2016b) took into consideration the effects of radiation in a second research work (Zeeshan and Majeed, 2016a, 2016b). The research conducted by Roy and Gorla (2017) was devoted to the mixed convection of unsteady MHD, a microfluidic fluid in the presence of thermal radiation and a heat source. Abdulhameed et al (2015) give an analytical solution (modified homotopy perturbation method) to the two-dimensional problem of the Falkner–Skan MHD boundary layer under the effect of a radiation source.…”
Section: Introductionmentioning
confidence: 99%